2022
DOI: 10.1021/acsabm.2c00663
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Family Nanomaterials for Stem Cell Neurogenic Differentiation and Peripheral Nerve Regeneration

Abstract: Stem cells play a critical role in peripheral nerve regeneration. Nerve scaffolds fabricated by specific materials can help induce the neurogenic differentiation of stem cells. Therefore, it is a potential strategy to enhance therapeutic efficiency. Graphene family nanomaterials are widely applied in repairing peripheral nerves. However, the mechanism underlying the pro-regeneration effects remains elusive. In this review, we first discuss the properties of graphene family nanomaterials, including monolayer an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 158 publications
(210 reference statements)
0
15
0
Order By: Relevance
“…The high mechanical strength and flexibility of GFNs make them ideal for microneedles that require precise and controlled insertion into the skin. 123 …”
Section: Biomedicine Application Of Gfnsmentioning
confidence: 99%
“…The high mechanical strength and flexibility of GFNs make them ideal for microneedles that require precise and controlled insertion into the skin. 123 …”
Section: Biomedicine Application Of Gfnsmentioning
confidence: 99%
“…reported GO to possess an inhibitory effect on AChE activity [25] . Recent literature also reports the advantageous effects of G/GO family of nanomaterials toward the enhancement of neural tissue engineering through the fabrication of nerve scaffolds [26] . Correspondingly, the superior electrical conductivity of these nanomaterials depicts their effectiveness as electrodes in neuronal migration pathways.…”
Section: Introductionmentioning
confidence: 99%
“…[25] Recent literature also reports the advantageous effects of G/GO family of nanomaterials toward the enhancement of neural tissue engineering through the fabrication of nerve scaffolds. [26] Correspondingly, the superior electrical conductivity of these nanomaterials depicts their effectiveness as electrodes in neuronal migration pathways. Another study by Qian et al reported the augmented efficiency of GO/polycaprolactone in axonal regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] In recent years, the emerging conductive material graphene and its derivatives have stood out in neural tissue engineering due to their outstanding physicochemical properties, including superior electrical and thermal conductivity, a large specific surface area, and excellent mechanical properties. 28,29 Among them, graphene-based materials have been shown to improve the adhesion, proliferation, and differentiation of various cells, including neural stem cells, as well as the germination and growth of neural synapses. 30,31 However, graphene is hydrophobic and has some cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%